2020
DOI: 10.3390/brainsci10110826
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in Relation to Depressive Disorders and Alcohol Abuse

Abstract: Chronic pain disorders have been associated separately with neuropsychiatric conditions such as depression and alcohol abuse. However, in individuals who suffer from non-cancer chronic pain disorders, it is not clear if the burden of depressive disorders is similar for those with and without a history of alcohol abuse. Using data from the Collaborative Psychiatric Epidemiology Surveys (CPES), we found depressive disorders to have a high burden in men and women with a history of alcohol abuse, independently of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…However, it is not clear whether psychiatric comorbidities burden on endometriosis or whether they are the consequence of painful symptoms. Nevertheless, it is not difficult to figure out that chronic pain as well as impaired psychological well-being may encourage alcohol misuse 60,61 . Alcohol consumption could be framed as a possible wrong selfmedication to cope with either stressful or painful events.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether psychiatric comorbidities burden on endometriosis or whether they are the consequence of painful symptoms. Nevertheless, it is not difficult to figure out that chronic pain as well as impaired psychological well-being may encourage alcohol misuse 60,61 . Alcohol consumption could be framed as a possible wrong selfmedication to cope with either stressful or painful events.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also revealed that alcohol intake by males with depressive symptoms did not significantly differ between the non-CP and CP groups. A cohort study by Maleki et al [ 41 ] reported a relationship between depression and CP with or without alcohol abuse. The novel result of the present study is that depression and CP were associated with a low alcohol intake.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospect, this seems a substantial oversight. For example, the neurobiology of both chronic pain and harmful alcohol use (e.g., Alcohol Use Disorder) are interrelated in terms of etiological and neurobiological factors 21,45,46 .…”
Section: Discussionmentioning
confidence: 99%